New uses of music: an analysis based on indie music in Buenos Aires - Boix, Ornela Alejandra (2019)
During the 2000s, the term “indie” became common and relatively principal for the juvenile, urban music of the metropolitan area of Buenos Aires. How can we understand the indie phenomenon in the history of juvenile music related to Argentine rock bands? What variables should we take into consideration to comprehend indie since its logic differs from the one established by the identitarian appropriation of music genres? In order to answer these questions, we describe indie music in Buenos Aires and show its evolution. We suggest that indie is much more than a way in which people identify themselves with music. It is the manifestation of a new relation with music and its means of production. In line with this idea, we explore the most recent pragmatic approach to “music into action” and music as mediator of the social to reformulate the notion of music to use.